Methane Adsorption Characteristics of Activated Carbon - Jin*, Hangkyo; Cho, Deug-Hee (Asian Journal of Chemistry, 2011)
Methane adsorption on activated carbons was investigated in the present works up to 70 bars at 298 K. Coconut-shell was activated by potassium hydroxide, resulting in activated carbons with different porosities. Methane adsorption isotherms show type 1 shape. The complete reversibility and fast kinetics of methane adsorption show that most of the adsorbed quantity is due to physical adsorption. Methane adsorption capacities are linear function of microporosities such as specific surface area, micropore surface area, total pore volume and micropore volume. The maximum methane adsorption capacity of 22 wt. % at 70 bars, 298 K is obtained in these materials.